Contact herbicides combined with mineral oil to control dayflower weeds - Leite, Tomaz Marques; Miranda, Gustavo Rabelo Botrel; Medeiros, Willis dos Santos; Botrel, Priscila Pereira; Alves, Alberto Donizete (Revista Agrogeoambiental, 2020)
Dayflower weeds are tolerant to some herbicides; an alternative for their control is the addition of adjuvants in the solution to be applied to improve the efficiency of these products. Thus, the objective of this work was to evaluate the effect of application of different herbicides with and without adjuvants on the control of dayflower weeds. The experiment was conducted under field conditions in April 2015 on the Santo Azarias Farm, Muzambinho, state of Minas Gerais, Brazil. The area had coffee crops (cultivar Catuaí/Vermelho 144) with plant spacing of 3.00 m × 1.00 m, which had been subjected to a hard pruning. A randomized block experimental design was used, with 9 treatments in 3 blocks, totaling 27 plots. The treatments consisted of four contact herbicides (Saflufenacil 700.0 g kg-1, at 140.0 g c.p. ha-1; Bentazon 600.0 g L-1, at 1.2 L c.p. ha-1; Paraquat 200.0 g L-1, at 3.0 L c.p. ha-1; and MSMA 720.0 g L-1, at 4.0 L c.p. ha-1) and an adjuvant (Nimbus®, mineral oil, 428.0 g L-1) at the rate of 0.3% of the solution volume. The plants in the treatments were evaluated visually by three people every three days, using a scale of grades of control. The plants were weighed every seven days after application of the herbicides to evaluate the percentage of water loss. The treatments MSMA, and MSMA combined with mineral oilpresented the best results for the control of dayflower weeds.